2022
DOI: 10.17161/kjm.vol15.15984
|View full text |Cite
|
Sign up to set email alerts
|

Suture Education with Soft-Embalmed Cadavers: A Cut Above the Rest

Abstract: Introduction. Assess the efficacy of a surgical skills curriculum for third-year medical students focused on suturing training on soft embalmed cadavers, which simulate natural tissue more effectively for surgical procedures than traditionally preserved cadavers or surgical practice pads.   Methods. We performed a retrospective cohort study comparing pre- and post-survey results at a premier, accredited, nationally ranked academic medical center. Study participants were third-year medical students completing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…3,14,27 Braasch et al demonstrated positive learning when students used softtissue cadavers versus synthetic skin. 28 Recruiting faculty can be challenging to implement, but some programs have demonstrated success using peer teaching and senior medical students to instruct junior medical students on proper suturing techniques. 8,17,[29][30][31]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,14,27 Braasch et al demonstrated positive learning when students used softtissue cadavers versus synthetic skin. 28 Recruiting faculty can be challenging to implement, but some programs have demonstrated success using peer teaching and senior medical students to instruct junior medical students on proper suturing techniques. 8,17,[29][30][31]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the positive impact of remote suture training, and student-directed teaching compared with faculty-directed teaching 3,14,27 . Braasch et al demonstrated positive learning when students used soft-tissue cadavers versus synthetic skin 28 . Recruiting faculty can be challenging to implement, but some programs have demonstrated success using peer teaching and senior medical students to instruct junior medical students on proper suturing techniques 8,17,29–31 …”
Section: Discussionmentioning
confidence: 99%